[Sketch of Potential Addition to the Dexter Library] - P. K. Phillips::::::photographer::: (1971)
A sketch of the potential addition to the Dexter library (Building 34). These plans were part of the initial proposal for the building, before the architectural plans for Kennedy Library were updated.